Analysis of Pathogens of Urinary Tract Infections Associated with Indwelling Double-J Stents and Their Susceptibility to Globularia alypum - Khaireddine Bouassida; Manel Marzouk; Sahar Nouir; Rim Ghammem; Wissal Sahtout; Meriam Ghardallou; Neila Fathallah; Jalel Boukadida; Mehdi Jaidane; Raoudha Slim; Amira Zaïri (MDPI AG, 2023)
Ureteral double-J stents are frequently used to prevent urinary obstruction. They can develop bacterial colonization and encrustation, which leads to persistent infections that seldom respond to antibiotic treatment. Thus, the goal of this study was to evaluate the local spectrum of bacterial pathogens and their susceptibility to natural compounds. A total of 59 double-J ureteral stents from 59 consecutive patients were examined. The samples were inoculated on agar culture mediums. Extracts of Globularia alypum L. were evaluated for their antibacterial activity with the diffusion and broth dilution methods; for antibiofilm activity, the crystal violet assay was used. The identification and the quantification of the different constituents of extracts were determined by reverse-phase high-performance liquid chromatography (RP-HPLC). Bacterial growth was found in three patients (5.1%). Enterococcus faecalis (1.7%), Acinetobacter baumanii (1.7%), and Pseudomonas putida (1.7%) strains were more commonly detected. They were resistant to several common antibiotics. All extracts presented several components, mainly nepetin-7-glucoside and trans-ferulic-acid, and they had antibacterial activity (MIC = 6.25 mg/mL and MBC = 6.25 mg/mL), and antibiofilm (59.70% at 25 mg/mL) properties, especially against Acinetobacter baumanii. The results achieved confirm the important role of this plant as a source of therapeutic activities.